Perancangan Aplikasi Online Course Menggunakan API Midtrans Sebagai Payment Gateway Berbasis Android - Ahmad Masrud Mubarok; Eva Handriyantini (Prosiding SISFOTEK, 2021)
Pusat Pelatihan Teknologi Informasi dan Komputer (PPTIK) STIKI Malang is an institution that organizes courses and training in the field of Information and Communication Technology (ICT). Courses and training programs at PPTIK STIKI Malang are held face-to-face, where PPTIK STIKI Malang provides the place, facilities and infrastructure to held it. Therefore, a mobile learning platform is needed that can be used to access course learning by online. Online course is one of the platforms that can be used as learning media. With the online course application, teaching materials can be accessed online anytime and anywhere. Although learning is held online, there are still costs that must be incurred by students to purchase course packages and access learning materials online. Therefore, a secure and practical online payment transaction technology is also needed. Midtrans is one of the payment gateway technologies in Indonesia that facilitates online payment transactions with complete payment methods such as bank transfers, e-wallet and others. By utilizing both technologies above, PPTIK STIKI Malang can increase the course learning services and minimize the use of place, time and cost along provide secure and complete payment transactions, so that can be easier for public to access course learning and purchase course.